FACTORS INFLUENCING CONSUMER PURCHASE INTENTION WHILE BUYING ONLINE - Baeshen, Yasser Ali (International Journal of Research -GRANTHAALAYAH, 2021)
Motivation/Background: Today, it is very imperative to study the factors that effect and predict the purchase intention of consumer online shopping. E-tailers and e-commerce is expanding very quickly, especially clothing and fashion brands have shifted to electronic channels to reach out their clients. This is one of the reasons that apparel is amongst the most sold items online. The purpose of this research is to identify the factors that influence consumer choices and which factors have significant effect on consumer purchase intention while online shopping fashion apparel. Method: This research has adopted quantitative approach and explanatory research purpose to establish relationship between four independent variables: Convenience, Price, Information and Security on the dependent variable (Consumer purchase intention). Survey response from 300 consumers was collected through online questionnaire and distributed through convenience sampling. Results: Data collected was analyzed on SPSS. For two hypotheses, correlation test one-sample t-test was conducted. Further, two hypothesis were analyzed by regression analysis. All four hypotheses were accepted. Results conclude that there is a significant relationship between online purchase intention of consumer and its factors such as price, convenience, security and information about product or service. Conclusions: This study has many implications for small retailers to focus on factors that can make it easier selling online. Security measures to protect user data are very vital to bring user back on the e-tailing website or webpage.